JETSU (Explore The Solar System): Student Education Application for Science Science Material for Junior High School Grade 7 - Nuriyah, Zidah Chotamy; Ramadhan, Ahmad Havi; Sholihah, Mufidatus (Proceeding International Conference on Education, 2023)
Interactive learning media that integrate aspects can make visual learning clearer. The result of this study is a set of learning programs that can be used as teaching tools. This research uses a type of R&D (Research and Development) research using the ADDIE model. In the development stage, researchers prepare sheets for validation to experts and tested to grade VII students. This research produced the following findings: (1) Development of android-based physics learning media on solar system materials; (2) With an average percentage of 88.33%, material experts, media experts, and material experts can evaluate the feasibility of learning media based on the results of argumentation and testing questionnaires, and can conclude that the media is in accordance with the criteria for use of "Eligible". And tests were conducted on seventh-graders who were in areas near the researcher's home, and were assessed by an average percentage.